â€œ The Effect of Conctraceptive Users and Per Capita Income on population Growth of West Kalimantanâ€ - B01112084, Eka Darwati (Jurnal Pembangunan dan Pemerataan, 2016)
This Reseacrch is entiltled â€œThe Effect of Contraceptive Users and Per Capita Income on Population Growth of West Kalimantanâ€. The reseacrh aims to examine and analyze the effect of the contraceptive users and per capita income on the population growth in West Kalimantan, either simultaneously or partially.The data analysis techinique used in this research was multiple regression using panel data (combination of time series and cross-section data) with fixed effect model approach. A total of 112 observations made to collect data at 14 regencies/cities in West Kalimantan from 2006 to 2013.Based on analysis, simultaneously contraceptive users and per capita income had a significant effect on the population growth in West Kalimantan, while partially contraceptive users and per capita income had a positive effect on the population growth in West Kalimantan.Keyword: population growth, contraceptive users, and per capita income